Venetoclax: evidence to date and clinical potential - Juárez-Salcedo, Luis Miguel; Desai, Viraj; Dalia, Samir (Drugs in Context, 2019)
The emergence of targeted therapy for patients with hematological diseases has permanently altered the therapeutic landscape. Immunochemotherapy regimes are now more and more being replaced by targeted therapies due to superior efficacy and better safety profiles. However, evolution and selection of subclones with continuous treatment leads to disease relapse and resistance toward these novel drugs. Venetoclax, the highly selective BCL-2 inhibitor (ABT-199), has an acceptable safety profile. To date, it has been approved for the treatment of first-line and relapsed/refractory chronic lymphocytic leukemia (CLL) and acute myeloid leukemia (AML). However, extension of indications can be expected in monotherapy and in combination regimens with promising outcomes in other hematological diseases. In this article, we describe the mechanism of action that stands behind the efficacy of venetoclax and provide a summary of available results from clinical trials.The emergence of targeted therapy for patients with hematological diseases has permanently altered the therapeutic landscape. Immunochemotherapy regimes are now more and more being replaced by targeted therapies due to superior efficacy and better safety profiles. However, evolution and selection of subclones with continuous treatment leads to disease relapse and resistance toward these novel drugs. Venetoclax, the highly selective BCL-2 inhibitor (ABT-199), has an acceptable safety profile. To date, it has been approved for the treatment of first-line and relapsed/refractory chronic lymphocytic leukemia (CLL) and acute myeloid leukemia (AML). However, extension of indications can be expected in monotherapy and in combination regimens with promising outcomes in other hematological diseases. In this article, we describe the mechanism of action that stands behind the efficacy of venetoclax and provide a summary of available results from clinical trials.